2013
DOI: 10.1590/s1413-70542013000400002
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocyanic acid content and growth rate of sorghum x sudangrass hybrid during fall

Abstract: In central Brazil after soybean or other annual agricultural species is harvested, sorghum hybrids are planted in the fall in order to establish pastures for grazing animals. This study conducted for two consecutive years aimed at quantifying the contents of hydrocyanic acid in the leaves and determining plant height, forage dry matter yield and the leaf/stem ratio for sorghum hybrid 1P400 at different ages. Statistical analysis was performed by regression analysis based on plant age. Leaf HCN content decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
0
6
0
1
Order By: Relevance
“…Kandungan HCN pada rumput gajah (Pennisetum purpureum) tergantung dari musim, dimana kandungan pada saat musim hujan lebih tinggi dibandingkan dengan musim kemarau, meskipun tidak berbeda jauh. Rata-rata kandungan HCN pada rumput gajah adalah 1,58 mg/100g (Onyeonagu et al, 2013 (Pickrell et al, 1991) tetapi kandungan tersebut akan menurun seiring dengan umur tanaman (Etuk et al, 2012;Simili et al, 2013).…”
Section: Hidrogen Sianida Dalam Bahan Pakan Ternakunclassified
“…Kandungan HCN pada rumput gajah (Pennisetum purpureum) tergantung dari musim, dimana kandungan pada saat musim hujan lebih tinggi dibandingkan dengan musim kemarau, meskipun tidak berbeda jauh. Rata-rata kandungan HCN pada rumput gajah adalah 1,58 mg/100g (Onyeonagu et al, 2013 (Pickrell et al, 1991) tetapi kandungan tersebut akan menurun seiring dengan umur tanaman (Etuk et al, 2012;Simili et al, 2013).…”
Section: Hidrogen Sianida Dalam Bahan Pakan Ternakunclassified
“…Excessive prussic acid content will cause poisoning in cattle where hemoglobin cannot bind oxygen in the blood. The content of prussic acid is above 1,000 mg/kg of dry matter (Simili et al, 2013). The purpose of this study was to determine the effect of sorghum varieties and harvesting time of sorghum planted in stylosanthes pastures base on growth, production and prussic acid content.…”
Section: Issn-0126-4400/e-issn-2407-876xmentioning
confidence: 99%
“…The ratio of Super-2 stems and leaves was 1.96, while BMR was 2.74. Simili et al (2013) stated that sorghum is cut when plant height is between 90 to 100 cm, with a stem and leaf ratio of 0.8 to 1.5 and a low prussic acid content. The results of statistical analysis showed that harvesting time had a significant effect (P<0.05) on the prussic acid content.…”
Section: Prussic Acid Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…These cuts occurred according to the recommendation for the crop, after reaching 50 cm in height (Neumann et al 2010). This is because young plants contain durrina, which turns into hydrocyanic acid in the rumen, making them toxic (Tamele et al 2009;Simili et al 2013).…”
Section: Introductionmentioning
confidence: 99%